2021
DOI: 10.3390/su13158359
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Propagated Summer Apples: Great Morphological and Biochemical Diversity

Abstract: The northeastern Anatolia region of Turkey is one of the richest plant biodiversity areas in Turkey. This study describes some important tree and fruit characteristics of 20 seed-propagated summer apple genotypes from northeastern Anatolia using morphological and biochemical markers. The genotypes were evaluated morphologically for tree growth habit, ripening date, fruit weight, fruit firmness, fruit shape, fruit color, fruit taste, juiciness and aroma. The biochemical characteristics measured were organic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
1
0
1
Order By: Relevance
“…These values were 3.81, 12%, 0.39% in Starking Delicious cv, respectively. Compared to previous studies [2,4,8,[28][29][30][31], our results are both suitable for the genus Malus and agree with previous findings. However, all quality parameters, the variation among genotypes was found to be significantly different and the parameter values were distributed over a wide scale.…”
Section: Fruit Quality Parameterssupporting
confidence: 91%
See 1 more Smart Citation
“…These values were 3.81, 12%, 0.39% in Starking Delicious cv, respectively. Compared to previous studies [2,4,8,[28][29][30][31], our results are both suitable for the genus Malus and agree with previous findings. However, all quality parameters, the variation among genotypes was found to be significantly different and the parameter values were distributed over a wide scale.…”
Section: Fruit Quality Parameterssupporting
confidence: 91%
“…According to Kim et al (2020) [43], total sugar content ranged from 71.2 to 134.4 g kg −1 fresh weight, fructose was the major sugar, major organic acid in apple juice was malic acid, which ranged from 413 to 2984 mg kg −1 fw, followed by citric acid and shikimic acid for 24 apple cultivars. Karatas et al (2021) [29], reported that apple fruits are known for their low vitamin C concentration and found low vitamin C content ranging from 5.6 to 9.3 mg 100 g −1 in 20 summer apple genotypes compared to our study. Macit et al (2021) [7], found that vitamin C varied from 2.31 to 7.66 mg 100 g −1 for investigated 8 local apple varieties.…”
Section: Organic Acids Sugars and Vitamin Ccontrasting
confidence: 46%